2020
DOI: 10.18231/j.pjms.2020.028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of ultrasound guided erector spinae plane block and oblique subcostal transversus abdominis plane block for postoperative analgesia in laparoscopic cholecystectomy

Abstract: Laparoscopic cholecystectomy (LC) is a commonly performed minimally invasive surgery. LC can cause moderate to severe postoperative pain due to small keyhole entries on the abdominal wall. The oblique subcostal transversus abdominis plane block (OSTAP) has been used for postoperative analgesia after LC but found not so effective. Our aim is to compare the effectiveness of erector spinae block with OSTAP block for postop analgesia after LC. Materials and Methods: This prospective, randomized study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…In the present study, the patients in group O demanded tramadol significantly more times than those in group E, and the first analgesic demand was significantly delayed in group E (p < 0.001). These results are similar to the above three studies [ 11 - 13 ]. Shahid et al conducted a study comparing the effects of paracetamol and tramadol on postoperative pain and found that the use of tramadol significantly increases the incidence of PONV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the patients in group O demanded tramadol significantly more times than those in group E, and the first analgesic demand was significantly delayed in group E (p < 0.001). These results are similar to the above three studies [ 11 - 13 ]. Shahid et al conducted a study comparing the effects of paracetamol and tramadol on postoperative pain and found that the use of tramadol significantly increases the incidence of PONV.…”
Section: Discussionsupporting
confidence: 93%
“…In another study conducted by Routray et al, it was concluded that rescue analgesic paracetamol consumption was lower in the ESPB group and the time to the first rescue analgesia request was longer in the ESPB group. This difference was found to be statistically significant; the results of which are persistent to the findings of the present study [ 11 ]. In a study conducted by Ozdemir et al, it was concluded that intra-operative and postoperative fentanyl requirements were lower in ESPB and the time to first rescue analgesic need was longer in ESPB.…”
Section: Discussionsupporting
confidence: 85%